2020
DOI: 10.1111/jcpe.13365
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term outcomes of osteotome sinus floor elevation without grafting in severely atrophic maxilla: A 10‐year prospective study

Abstract: Objective: The aim of the present study was to report 10-year results of osteotome sinus floor elevation (OSFE) without grafting severely atrophic maxilla (residual bone height ≤4 mm). Materials and Methods: Patients undergoing OSFE without grafting and implant placement were included for 10-year examinations. Implant survival, complicationfree survival, modified bleeding index (mBI), modified plaque index (mPI), pocket probing depth (PPD), peri-implant marginal bone loss (MBL), endo-sinus bone gain (ESBG) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 30 publications
0
27
0
Order By: Relevance
“…Low RBH was detected to significantly increase late implant loss at TSFE sites. With the development of dental devices and clinical skills, the indications of TSFE have gradually expanded (Al‐Dajani, 2016; Gonzalez et al, 2014; Shi et al, 2020). For example, an RCT demonstrated that implant placed simultaneously with TSFE had a comparable survival rate to those placed after LSFE for sites of RBH <6 mm (Zhou et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Low RBH was detected to significantly increase late implant loss at TSFE sites. With the development of dental devices and clinical skills, the indications of TSFE have gradually expanded (Al‐Dajani, 2016; Gonzalez et al, 2014; Shi et al, 2020). For example, an RCT demonstrated that implant placed simultaneously with TSFE had a comparable survival rate to those placed after LSFE for sites of RBH <6 mm (Zhou et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…When it came to SFA, the most concerned outcomes were implant survival, complications, 2D radiographic bone gain/changes, 3D radiographic bone gain/changes, and MBLs, while PROMs and peri‐implant clinical parameters were seldom reported. SFA has been reported as a predictable technique in the posterior maxilla with limited bone height (Raghoebar et al, 2019; Shi et al, 2020). Thus, studies on SFA nowadays focus more on detecting potential risks and avoiding complications.…”
Section: Discussionmentioning
confidence: 99%
“…The total cumulative treatment cost included the cost relate to initial treatment and additional expenses for management of technical and biological complications experienced during the 3‐year follow‐up. Cost was determined by the actual fee of the necessary procedures derived from guided price by local government in Shanghai (Shi et al, 2020).…”
Section: Methodsmentioning
confidence: 99%